What's in Your Space? : 5 Steps for Better School and Classroom Design - Carter, Dwight; Sebach, Gary; White, Mark (Thousand Oaks, California ; Corwin A SAGE Company, 2016)
Transformed learning spaces begin with transformed thought Educators know they must incorporate skills for the global economy, adapt to diverse learning styles, and employ technology. But what about our physical spaces? How can or should they change to reflect 21st Century teaching models? Walk with the group behind one of America's most recognized school redesign projects and discover how to design both "thinking" ....
Includes index
Keywords: Classroom -- Planning; Classroom environment; Education and globalization